1994
DOI: 10.1088/0953-8984/6/46/026
|View full text |Cite
|
Sign up to set email alerts
|

On the field-dependent magnetic structures of CsCuCl3

Abstract: Neutron diffraction results on single crystals of CsCuCl3 in high magnetic fields are reported. The fields were applied parallel (up to about 6.5 T) and perpendicular (up to 8.5 T) to the c axis of the hexagonal crystal. For the parallel field a spin-flop-like change in the magnetic structure at fields above 5.6 T was observed close below the Neel temperature. The magnetic phase diagram has been determined in the temperature range between 9.6 K and TN=10.675 K. In the perpendicular field the magnetic satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 17 publications
4
24
0
Order By: Relevance
“…The discontinuity [13][14][15] in the low-T magnetization at H ≈ 0.4 H S was shown by Nikuni and Shiba 16,17 to be a novel, fluctuationinduced phase transition from the umbrella structure (optimal at small H due to a small, easy-plane anisotropy 18 in the intrachain exchange) to a coplanar structure (optimal at larger H due to quantum fluctuations). Further experiments [19][20][21][22][23] , including neutron-diffraction 24 and specific-heat measurements 12 near T N , confirmed their analysis.…”
Section: Introductionsupporting
confidence: 58%
“…The discontinuity [13][14][15] in the low-T magnetization at H ≈ 0.4 H S was shown by Nikuni and Shiba 16,17 to be a novel, fluctuationinduced phase transition from the umbrella structure (optimal at small H due to a small, easy-plane anisotropy 18 in the intrachain exchange) to a coplanar structure (optimal at larger H due to quantum fluctuations). Further experiments [19][20][21][22][23] , including neutron-diffraction 24 and specific-heat measurements 12 near T N , confirmed their analysis.…”
Section: Introductionsupporting
confidence: 58%
“…Mekata et al obtained β = 0.25±0.01 while Stüsser et al obtained [102] β = 0.23 ± 0.02, which were close to the n = 2 chiral value and that of CsMnBr 3 . By contrast, Weber et al observed in the temperature range 10 −3 <| t |< 5 × 10 −2 a power-law scaling behavior in the specific heat characterized by α = 0.35 ± 0.05 and A + /A − = 0.29 ± 0.05 close to the n = 2 chiral values, but observed a deviation from this scaling behavior in a closer vicinity of T c .…”
Section: (B) Helimagnetssupporting
confidence: 52%
“…CsCuCl 3 exhibits field-induced phase transition for H c, which is caused by the competition between planar anisotropy and quantum fluctuation. [2][3][4] A small amount of Co 2+ doped in CsCuCl 3 produces successive magnetic phase transitions, 5) and the low-temperature phase was found to be an oblique triangular antiferromagnetic phase in which spins form triangular structure in a plane tilted from the basal plane.…”
Section: §1 Introductionmentioning
confidence: 99%